The Role of Exosomal Non-Coding RNAs in Coronary Artery Disease - Jia Liu; Junduo Wu; Longbo Li; Tianyi Li; Junnan Wang (Frontiers Media S.A., 2020)
Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality worldwide. Atherosclerosis (AS) is a major cause of CVD. Oxidative stress, endothelial dysfunction, and inflammation are key factors involved in the development and progression of AS. Exosomes are nano-sized vesicles secreted into the extracellular space by most types of cells, and are ideal substances for the transmission and integration of signals between cells. Cells can selectively encapsulate biologically active substances, such as lipids, proteins and RNA in exosomes and act through paracrine mechanisms. Non-coding RNAs (ncRNAs) are important for communication between cells. They can reach the recipient cells through exosomes, causing phenotypic changes and playing a molecular regulatory role in cell function. Elucidating their molecular mechanisms can help identify therapeutic targets or strategies for CVD. Coronary artery disease (CAD) is the most important disease in CVD. Here, we review the role and the regulatory mechanism of exosomal ncRNAs in the pathophysiology of CAD, as well as the potential contribution of exosomal ncRNA to diagnosis and treatment of CAD.